2019
DOI: 10.1016/j.tranon.2019.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Pharmacokinetic and Safety Studies of Copper-Diacetyl-Bis(N4-Methylthiosemicarbazone) (Cu-ATSM): Translational Studies for Internal Radiotherapy

Abstract: Hypoxia plays important roles in the prognosis of malignant brain tumors such as glioblastoma because it causes drug delivery deficiencies and the induction of hypoxia-inducible factor-1α in tumor cells. Extensive hypoxic areas are associated with poor prognosis of these fatal diseases. We previously reported that multiple administrations of the hypoxia-targeted internal radiotherapy agent 64 Cu-diacetyl-bis( N 4 -methylthiosemicarbazone) ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…Similar therapeutic effects has also been demonstrated with [ 64 63 Cu and 65 Cu) and free H 2 -ATSM in a preclinical mouse study. Therapeutic administration of stable [Cu(ATSM)] and H 2 -ATSM in a ratio of 2:25 was found to be safe for patients when given as 15 μg once per week for 4 weeks [63]. In addition, [ 64 Cu][Cu(ATSM)] therapy have been shown to be a novel approach to enhance cancer treatment efficiency concomitantly with bevacizumab in a human colon carcinoma xenograft model, where the repeated use of bevacizumab has caused decreased tumor vascularization and tumor hypoxia.…”
Section: Role Of Cu-64 In Therapeutic Applicationssupporting
confidence: 76%
See 1 more Smart Citation
“…Similar therapeutic effects has also been demonstrated with [ 64 63 Cu and 65 Cu) and free H 2 -ATSM in a preclinical mouse study. Therapeutic administration of stable [Cu(ATSM)] and H 2 -ATSM in a ratio of 2:25 was found to be safe for patients when given as 15 μg once per week for 4 weeks [63]. In addition, [ 64 Cu][Cu(ATSM)] therapy have been shown to be a novel approach to enhance cancer treatment efficiency concomitantly with bevacizumab in a human colon carcinoma xenograft model, where the repeated use of bevacizumab has caused decreased tumor vascularization and tumor hypoxia.…”
Section: Role Of Cu-64 In Therapeutic Applicationssupporting
confidence: 76%
“…It was found that exposure of [ 64 Cu]CuCl 2 inhibits the neurosphere-forming ability of tumor cells, a prerequisite for the formation of tumor masses [29]. Similar therapeutic effects has also been demonstrated with [ 64 63 Cu and 65 Cu) and free H 2 -ATSM in a preclinical mouse study. Therapeutic administration of stable [Cu(ATSM)] and H 2 -ATSM in a ratio of 2:25 was found to be safe for patients when given as 15 μg once per week for 4 weeks [63].…”
Section: Role Of Cu-64 In Therapeutic Applicationssupporting
confidence: 53%
“…2b) is a biosimilar and only releases the exogenously bound Cu under hypoxic conditions. Both Cu-ATSM and ATSM are quickly cleared from the circulation with corresponding half-lives (T 1/2 ) of 21.5 and 22.4 min, respectively [38]. The BBB is a highly selective gateway regulating the influx and efflux of molecules from the systemic circulation into the brain and in the reverse direction.…”
Section: Cu-atsm In Imaging Cancers and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Administration of penicillamine, a heavy metal chelator, could reduce radiation absorption doses in critical organs such as the liver and small intestine [72]. Different formulations of [ 64 Cu]Cu-ATSM have been developed and validated by two research groups for diagnostic and theranostic applications, respectively [38,63]. The potential risk associated with the chemical impurities from [ 64 Cu]Cu-ATSM degradation is negligible, even in a therapeutic dose of [ 64 Cu]Cu-ATSM [73].…”
Section: Cu-atsm In Imaging Cancers and Neurodegenerative Diseasesmentioning
confidence: 99%